MiR-144-3p Enhances Cardiac Fibrosis After Myocardial Infarction by Targeting PTEN - Yuan, Xiaolong; Pan, Jinchun; Wen, Lijuan; Gong, Baoyong; Li, Jiaqi; Gao, Hongbin; Tan, Weijiang; Liang, Shi; Zhang, Hao; Wang, Xilong (Frontiers in Cell and Developmental Biology, 2019)
Myocardial infarction (MI) may cause heart failure and seriously harm human health. During the genesis of cardiac fibrosis after MI, the proliferation and migration of cardiac fibroblasts contribute to secretion and maintenance of extracellular matrix (ECM) components. Many miRNAs have been highly implicated in the processes of cardiac fibrosis after MI. However, the molecular mechanisms for how miRNAs involve in cardiac fibrosis remain largely unexplored. Based on MI model in miniature pigs, the potential miRNAs involved in MI were identified by using small RNA sequencing. Using human cardiac fibroblasts as a cellular model, EdU, Transwell, and the expression of ECM-related proteins were applied to investigate the cell proliferation, migration and collagen synthesis. In this study, using MI model based on miniature pigs, 84 miRNAs were identified as the differentially expressed miRNAs between MI and control group, and miR-144-3p, one of differentially expressed miRNAs, was identified to be higher expressed in infarct area. The cell proliferation, migration activity, and the mRNA and protein levels of the ECM-related genes were significantly increased by miR-144-3p mimic but significantly decreased by miR-144-3p inhibitor in cardiac fibroblasts. Furthermore, miR-144-3p was observed to repress transcription and translation of PTEN, and interfering with the expression of PTEN upregulated the mRNAs and proteins levels of α-SMA, Col1A1, and Col3A1, and promoted the proliferation and migration of cardiac fibroblasts, which was in line with that of miR-144-3p mimics, but this observation could be reversed by miR-144-3p inhibitor. Collectively, miR-144-3p promotes cell proliferation, migration, and collagen production by targeting PTEN in cardiac fibroblasts, suggesting that miR-144-3p-mediated-PTEN regulation might be a novel therapeutic target for cardiac fibrosis after MI.